Study on feasibility of village survey based on SPOTS image - DING Xiao-dong; XU Hao; YU Zhi-qiang; ZHANG Zhong-chu; WANG Ke (浙江大学学报. 农业与生命科学版)
Feasibility and precision of village survey based on the SPOT5 image were discussed. One case study was taken in Longxiang section of Tongxiang city of Zhejiang Province. The village vector data of Longxiang at 1∶10000 scale was obtained from the SPOT5 image, and the patch area precision was analyzed with the synchronous aerial survey data. The results show that the patch interpretation precision of property was about 95%, the extracted patch area precision was above 85% when the patch area is above 500 m2, and the average extracted patch area precision was about 94%. These results indicate it's feasible to do village survey using SPOT5 image.